Analyzing genomic and epigenetic profiles in single cells by hybrid transposase (scGET-seq) - Davide Cittaro; Dejan Lazarević; Giovanni Tonon; Francesca Giannese (STAR Protocols, 2023)
Summary: scGET-seq simultaneously profiles euchromatin and heterochromatin. scGET-seq exploits the concurrent action of transposase Tn5 and its hybrid form TnH, which targets H3K9me3 domains. Here we present a step-by-step protocol to profile single cells by scGET-seq using a 10× Chromium Controller. We describe steps for transposomes preparation and validation. We detail nuclei preparation and transposition, followed by encapsulation, library preparation, sequencing, and data analysis.For complete details on the use and execution of this protocol, please refer to Tedesco et al. (2022)1 and de Pretis and Cittaro (2022).2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.